ANALISIS KINERJA EKONOMI WILAYAH PROVINSI SUMATERA BARAT - Syamsul Amar (Quantitative Economics Journal, 2016)
Macro regional variables are engine in regional economy. Regional economyactivity must be conducted by local resources and supported regulation from localgovernment. Each regency and municipality in West Sumatera have leading sectoreconomy. There are sevent regency/municipality led at primary sector, sixregency/municipality led at secondary sector and and four regency/municipalityled at tertiery sector. Leading sector economy as economic base created goods andservice mobility through interregional trade efficienly and income multiplier effectas well as labour multiplier effect continuously. Therefore, needed governmentpolicy to accomodate the public interest bese on local potential